2019
DOI: 10.1259/bjr.20190380
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy, prognostic variables and clinical outcome of 177Lu-PSMA-617 PRLT in progressive mCRPC following multiple lines of treatment: prognostic implications of high FDG uptake on dual tracer PET-CT vis-à-vis Gleason score in such cohort

Abstract: Objective: To evaluate the therapeutic response, progression free survival (PFS), overall survival (OS) and clinical toxicity of 177Lu-PSMA-617 PSMA targeted radioligand therapy (PRLT) in the setting of heavily pre-treated metastatic castrate-resistant prostate cancer (mCPRC) patients and also examine the association of prognostic variables with therapeutic outcome in such patient cohort. Methods: We examined the medical records of mCRPC patients who had undergone 177Lu-PSMA-617 PRLT from March 2017 to Februar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 29 publications
0
60
0
Order By: Relevance
“…[ 4 ] In a retrospective study of forty patients of mCRPC who failed on first-line treatment and received at least two cycles of 177 LuPSMA radioligand therapy, 21 (52.5%) had a symptomatic and biochemical response and 16 (43%) responded on molecular imaging, without any Grade 3 or 4 toxicity. [ 5 ] The most recent Phase II long-term outcome data on 90 patients in mCRPC with a median follow-up time of 28 months was published in January 2020[ 6 ] and showed median OS of 14 months and PFS of 11.8 months, similar to the index study[ 1 ] and with low toxicity.…”
Section: Commentsmentioning
confidence: 78%
“…[ 4 ] In a retrospective study of forty patients of mCRPC who failed on first-line treatment and received at least two cycles of 177 LuPSMA radioligand therapy, 21 (52.5%) had a symptomatic and biochemical response and 16 (43%) responded on molecular imaging, without any Grade 3 or 4 toxicity. [ 5 ] The most recent Phase II long-term outcome data on 90 patients in mCRPC with a median follow-up time of 28 months was published in January 2020[ 6 ] and showed median OS of 14 months and PFS of 11.8 months, similar to the index study[ 1 ] and with low toxicity.…”
Section: Commentsmentioning
confidence: 78%
“…The adverse side effects of chemotherapy such as myelosuppression, gastrointestinal and cardiac toxicity, neuropathy as well as alopecia have also to be weighed against the favorable side effects profile of PSMA treatment [1]. Despite its relevance, to date only fewer studies analyzed the influence of PSMA therapy on QoL [2,[17][18][19][20] and none of these studies closely examined the association between improvements in health-related QoL and changes in PSA. Our patient cohort consisted of 30 PSMA-treated patients, all of them were affected by bone metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The mean ECOG performance status improved from 2.5 to 1.8. Suman et al [18] reported findings in a total of 40 mCRPC patients who had undergone at least 2 cycles of PSMA. QoL was assessed by the ECOG score and Karnofsky index, no specific assessment of pain symptoms was performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). In a recently published study [24] that critically examined in the setting of [ 177 Lu]Lu-PSMA PRLT the value of [ 18 F]FDG uptake in an unselected subset of highly pretreated patients of mCRPC, there was an evident association of high [ 18 F]FDG uptake with increasing Gleason score and poorer 12-month progression-free survival (PFS), indicative of aggressive disease biology. When these patients were sub-divided into groups (Gp) as per the [ 18 F]FDG uptake (SUVmax) in the lesions (SUVmax values 0-7, 7.1-15 and ≥ 15.1), with approximately equal distribution of cases in each, patients with Gleason score 8 and above showed higher [ 18 F]FDG uptake (SUVmax > 7.1).…”
Section: Psma-directed Prlt: Can This Be Considered Early In Disease mentioning
confidence: 99%